Stability of hybrid airships - Asrar, Waqar (s.n, 2012)
The mathematical model of a winged hybrid airship is developed for the analysis of its dynamic stability characteristics. A full set of nonlinear equations of motion of the hybrid airship is determined and adequate assumptions are made in order to apply any relevant computation and estimation methods. The design of the hybrid airship is slightly modified to suit the demanding requirement of a complete and feasible mathematical model. Linearization is then performed under a chosen trim condition, and eigenvalue analysis is carried out to determine the general dynamic stability characteristics of the winged hybrid airship. The result shows that the hybrid airship possesses dynamic instability in longitudinal pitch motion and lateral-directional slow roll motion due to the strong coupling between the aerostatic lift from the buoyant gas and aerodynamic lift from the wing